Pediatric population (aged 3-11 years) received primary inactivated SARS-CoV-2 vaccination prior to infection exhibiting robust humoral immune response following infected with Omicron variant: a study conducted in Beijing - Li, Jing; Li, Jingjing; Dai, Shuzhi; Dang, Li; Wang, Lin; Cao, Ling; Chen, Xiaobo; Wang, Ying; Ge, Menglei; Liu, Weijie; Song, Qinwei; Xu, Wenjian; et al. (Frontiers in Immunology, 2023)
Objective: Analysis of SARS-CoV-2 IgG antibody and neutralizing antibody levels following SARS-CoV-2 infection in children aged 3-11 years, comparing those who had received the inactivated SARS-CoV-2 vaccine to those who were unvaccinated prior to infection, provides evidence for public health centers in formulating vaccination strategies and control policies.A study was conducted on children who visited the Children's Hospital, Capital Institute of Pediatrics from January 10, 2023 to March 31, 2023. Participants or their guardians completed a survey questionnaire providing information about their SARS-CoV-2 infection history and vaccination status. Serum samples were collected for testing of SARS-CoV-2 immunoglobulin G (IgG) and neutralizing antibodies (Nabs), which were performed using chemiluminescence immunoassay.The study included 1,504 children aged 3-11 years with previous SARS-CoV-2 infection. Among the 333 unvaccinated children, the serum SARS-CoV-2 IgG antibody level was median 2.30 (IQR, 1.27-3.99). However, children received one dose (78 cases) and two doses (1093 cases) of the inactivated vaccine prior to infection showed significantly higher SARS-CoV-2 IgG antibody levels, with values of median 10.11 (IQR, 8.66-10.93) and median 10.58 (IQR, 9.79-11.07), respectively. As to the unvaccinated children, 70.3% (234/333) were negative for SARS-CoV-2 Nabs less than 6.00AU/ml. The remaining 29.7% (99/333) showed relatively low levels of Nabs, ranging from 6.00 to 50.00AU/ml. In contrast, for children who had received two doses of vaccine prior to infection, an overwhelming 99.3% (1086/1093) exhibited high levels of Nas in the range of 100.00-120.00 AU/ml. Remarkably, these elevated Nab levels persisted for at least a period of 3 months post-infection in children who had received two doses of inactivated SARS-CoV-2 vaccine prior to infection, regardless of age or sex and vaccine manufacturer.The administration of two doses of inactivated SARS-CoV-2 vaccine prior to infection has been shown to significantly enhance humoral immunity following SARS-CoV-2 infection in pediatric populations, producing adequate Nabs that persist at elevated levels for up to 3 months postinfection. For unvaccinated children who displayed weak humoral immunity following a primary natural infection, timely vaccination is recommended to bolster their immunization protection. The findings underscore the importance of vaccination in strengthening immune responses and protecting pediatric populations against SARS-CoV-2 infection.